CONTEXTUALISING URBAN ENGINEERING EDUCATION FOR FUTURE CITIES - Dillip K DAS; Fidelis EMUZE (Journal of Construction Project Management and Innovation)
While rapidity in service activities have strengthened the role of urban areas as engines of economic growth, high population density and increased industrialization, has brought needless social and environmental complaints in cities. This phenomenon necessitates a change in societal attitude in f avor of the creation of responsible living conditions, which demands requisite skills and knowledge that would shape the cities. Thus, this paper explores the adequacy of current urban engineering education in terms of the knowledge, skills and competencie s required to plan and develop future cities. The paper examines how “wicked problems” that marginalize effective sustainable city planning can be addressed through astute understanding of social and environmental challenges, urban governance systems and s takeholder involvement. Based on current education system, initial findings suggest that competencies in urban planning will not necessarily enable students to address challenges related to the development of smart and sustainable cities. Rather, engineeri ng, science and social knowledge, which would engender the ability to predict future social dynamics, should enable graduates to become active drivers of sustainable and livable cities